Meditating selflessly : practical neural Zen - Austin, James H., 1925- (MIT Press, 2011)
This is not the usual kind of self-help book. Indeed, its major premise heeds a Zen master's advice to be less self-centered. Yes, it is "one more book of words about Zen," as the author concedes, yet this book explains meditative practices from the perspective of a " neural Zen." The latest findings in brain research inform its suggestions. In Meditating Selflessly, James Austin -- Zen practitioner, neurologist and author of three acclaimed books on Zen and neuroscience -- guides readers toward that open awareness already awaiting them on the cushion and in the natural world. Austin offers concrete advice -- often in a simplified question-and-answer format -- about different ways to meditate. He clarifies both the concentrative and receptive styles of meditation. Drawing widely from the exciting new field of contemplative neuroscience, Austin helps resolve an ancient paradox: why both insight wisdom and selflessness arise simultaneously during enlightened states of consciousness.